PENGEMBANGAN MULTIMEDIA INTERAKTIF PETA BILANGAN CACAH (PEBICA) BERBASIS ANDROID PADA MATERI SIFAT-SIFAT OPERASI HITUNG PADA BILANGAN CACAH DI SDN TAROKAN 3 - RAMADHAN, NOPRIZAL; PRIMASATYA, NURITA; HUNAIFI, ABDUL AZIZ (EDUTECH : Jurnal Inovasi Pendidikan Berbantuan Teknologi, 2024)
This research is a development research that aims to produce interactive multimedia in mathematics learning for students at SDN Tarokan 3, Kediri Regency and determine the quality of this interactive multimedia based on the assessment of media experts, material and learning experts. The development model used to develop interactive multimedia refers to the ADDIE development model, which includes 5 stages, namely 1) Analysis Stage, 2) Design Stage, 3) Development Stage, 4) Implementation Stage, 5) Evaluation Stage. Interactive multimedia that has been consulted and assessed by material experts and media experts. This interactive multimedia contains material on the properties of arithmetic operations on whole numbers for class 3. Map of Whole Numbers (PEBICA) based on an Android application on the material on the properties of arithmetic operations on whole numbers. The results of this research are as follows: interactive multimedia was declared very valid after validation by media experts and material experts with a score of 89% so it was classified as very valid criteria. From the results of the questionnaire, teacher and student responses to limited and extensive trials obtained a score of 90.5%, so it is classified as very practical. To see the effectiveness of interactive multimedia, it can be seen from the average learning outcome score of 87.75% and has exceeded the specified Maximum Completeness Criteria (KKM), namely 75. Thus, it can be concluded that the interactive multimedia Whole Number Map based on the Android application is effective for use in learning process. ABSTRAKPenelitian ini merupakan peneltian pengembangan yang bertujuan untuk menghasilkan multimedia interaktif dalam pembelajaran matematika pada siswa SDN Tarokan 3 Kabupaten Kediri dan mengetahui kualitas dari multimedia interaktif tersebut berdasarkan penilaian ahli media, ahli materi dan pembelajaran. model pengembangan yang digunakan untuk mengembangkan multimedia interaktif mengacu pada model pengembangan ADDIE, yang mencakup 5 tahapan yaitu 1) Tahap Analisis, 2) Tahap Design, 3) Tahap Pengembangan, 4) Tahap Implementasi, 5) Tahap Evaluasi. Multimedia interaktif yang telah dikonsultasikan dan dinilaikan kepada ahli materi dan ahli media. Multimedia interaktif ini memuat materi sifat-sifat operasi hitung pada bilangan cacah kelas 3. Penelitian pengembangan ini menghasilkan produk media pembelajaran multimedia interaktif Peta Bilangan Cacah (PEBICA) Hasil penelitian ini sebagai berikut: multimedia interaktif dinyatakan sangat valid setelah dilakukan validasi oleh ahli media dan ahli materi dengan skor perolehan 89% sehingga tergolong dalam kriteria sangat valid. Dari hasil angket respon guru dan siswa pada uji coba terbatas dan luas memperoleh skor perolehan 90,5% sehingga tergolong dalam kriteria sangat praktis. Untuk melihat keefektifan multimedia interaktif dilihat dari rata- rata nilai hasil belajar sebesar 87,75% dan telah melebihi Kriteria Ketuntasan Maksimal (KKM) yang telah ditentukan yaitu 75. Dengan demikian, dapat disimpulkan bahwa multimedia interaktif Peta Bilangan Cacah berbasis aplikasi android efektif digunakan dalam proses pembelajaran.